Platoon [videorecording (DVD)] - Stone, Oliver; Berenger, Tom, 1949-; Dafoe, Willem; Sheen, Charlie (MGM Home Entertainment Inc., 2006)
Follows young Chris Taylor who arrives in Vietnam and quickly discovers that his worst enemies are not just the Viet Cong, but gnawing fear, physical exhaustion, and the anger growing within himself.